The impact of GENBI SUL-TENG's socialization and implementation on Islamic Economics students' QRIS payment preference - Fikram; Irham Pakkawaru; Ferdiawan; Mochammad Syahfril Moharom (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
This study aims to determine the effect of socialization and implementation of Generasi Baru Indonesia Central Sulawesi (GenBi Sul-Teng) on the interest of students at the Faculty of Economics and Islamic Business in using non-cash payments through QRIS in Era 5.0, with convenience as a moderating variable, both partially and simultaneously. This research is an associative quantitative study utilizing a quantitative approach. Primary data were collected through observation and distribution of questionnaires, with all members of the population being included as samples. Data analysis techniques, classical assumptions, and MRA were performed using the SPSS version 23 for Windows program. The results indicate that, partially, through the T test, socialization variables have a positive and significant effect on student interest, and application variables also exhibit a positive and significant effect on student interest. Meanwhile, in the F test, both socialization and application variables simultaneously influence student interest. The convenience variable moderates the effect of socialization on student interest but is not significant. However, the convenience variable can moderate the effect of application on student interest, with the coefficient of determination (R Square) being 0.452. This implies that the independent variables' influence on the dependent variable in this study is 45.2%, while the remainder is influenced by other variables not examined.